Handheld imageless robotic total knee arthroplasty improves accuracy and early clinical outcomes when compared with navigation - Joshua Yeuk-Shun Tran; Abbie Yan-Tung Tang; Cham-Kit Wong; Gloria Yan-Ting Lam; Tsz-Lung Choi; Rex Wang-Fung Mak; Jonathan Patrick Ng; Kevin Ki-Wai Ho; Michael Tim-Yun Ong; Patrick Shu-Hang Yung (Arthroplasty)
Abstract Background This study compared imageless robotic-assisted total knee arthroplasty (RATKA) with accelerometer-based navigation (ABN) systems in terms of surgical accuracy and early clinical outcomes. Methods A retrospective analysis was conducted on 153 patients (178 knees) who had undergone primary TKA from 2017 to 2023. Surgical accuracy and functional outcomes were assessed up to 12 months post-operation using the Chi-square test, Student’s t-test, and ANCOVA. Subgroup analyses based on patient demographics were also conducted. Results Among 153 patients, 101 underwent RATKA, and 52 received ABN. RATKA demonstrated superior alignment accuracy with a significantly lower deviation from the planned alignment (P < 0.05). Additionally, RATKA led to significantly better postoperative functional scores at 6 weeks (P = 0.001) and 3 months (P = 0.001), even after adjusting for preoperative functional differences. Conclusions RATKA offers enhanced precision and improves early recovery compared to ABN, supporting its potential as a preferred technology for TKA. Its ability to optimize kinematic alignment may contribute to superior patient outcomes. Compared to ABN, RATKA provides a unique advantage by achieving greater accuracy in planned alignment, which may translate into improved functional recovery. Further research with larger cohorts is recommended to confirm these findings.